PHARMACOTHERAPEUTIC STRATEGIES FOR ENDOTHELIAL DYSFUNCTION CORRECTION WITH USE OF STATINES IN SYNDROME OF SYSTEMIC INFLAMMATORY RESPONSE - Tatiana Denisyuk (Belgorod National Research University, 2017)
Objectives: The ways of pharmacological correction of cardiovascular complications in the syndrome of the systemic inflammatory response (SIRS) are not fully developed. Goal: Determination of statins' new pharmacological effects and its combination with endothelioprotectors in the SIRS correction. Methods: In experiments on mice, rats and rabbits, the anti-inflammatory, cardioprotective and endothelioprotective effects of statins and endothelioprotectors were explored. The modeling of endotoxin-induced endothelial dysfunction (EIED) was created by infecting rats with Staphylococcus aureus (strain 13407), subcutaneously (60 billion microbial bodies). To determine the activity of the inflammatory process, the indices of the C-reactive protein used. The involvement of the cytokine link of inflammation was assessed according to the plasma levels of TNF-α and IL-6. Modeling of L-NAME-induced pathology and further evaluation of endothelial and endothelium-independent vascular reactions were carried through according to a standard protocol. Results. Simvastatin (9, 19, 35 mg/kg), atorvastatin (5, 9, 19 mg/kg), rosuvastatin (9, 19, 35 mg/kg) and nanoparticulated rosuvastatin (3, 6.3 and 11.6 mg/kg) proved a dose-dependent antiexudative effect on the model of formalin paw edema in mice. Similarly, the anti-inflammatory effect is evident in the exudative model on rabbits. The greatest effectiveness was demonstrated by rosuvastatin and its nanoparticularized form. Simvastatin 8.5 mg/kg, atorvastatin 4.3 mg/kg, rosuvastatin 8.5 mg/kg, and nanoparticulated rosuvastatin 11.6 mg/kg demonstrate a cardioprotective effect in the coronary-occlusive modeling of infarction in rats. In the process of cardioprotective effects' implementation the mechanisms of pharmacological preconditioning has significant importance. It was proved by the removal of effects with K + -ATP-as channels blockade with glibenclamide (5 mg/kg) and iNOS blockade with aminoguanidine (40 mg/kg). The use of inhibitors HMG-CoA reductase of simvastatin (2.2, 4.3 and 8.5 mg/kg), atorvastatin (1.1, 2.2 and 4.3 mg/kg), rosuvastatin (2.2, 4 , 3 and 8.5 mg/kg) and nanoparticulated rosuvastatin (3, 6.3 and 11.6 mg/kg) on the background of endotoxin-induced pathology modeling leads to the development of a dose-dependent endothelioprotective effect, which is expressed in normalization of coefficient of endothelial dysfunction (CED), to prevention of adrenoreceptivity increase and to the exhaustion of the myocardial reserve, as well as to the normalization of biochemical markers of inflammation (C-reactive protein) and the level of pro-inflammatory cytokines. At the same time, positive dynamics of the final products of NO and eNOS expression was defined. Applying of monotherapy with donator NO L-arginine (70 and 200 mg/kg), a nonselective inhibitor of arginase BEC (5 and 10 mg/kg), a selective inhibitor of arginase-2 arginasine (1 and 3 mg/kg) and recombinant darbepoetin (50 and 500 μg/kg) in the modeling of endothelial dysfunction, has revealed their high activity, expressed in preventing the increase in CED, adrenoreactivity, preservation of the myocardial reserve and normalization of the values ​​of biochemical markers (Total NO, eNOS expression, C-reactive protein, IL-6, TNF). Herewith, the drugs had a dose-dependent effect and were approximately equally effective. A vector analysis of the additive effects of the combined use of inhibitors of HMG-CoA reductase, simvastatin, atorvastatin, rosuvastatin and nanoparticulated rosuvastatin with L-arginine, inhibitors of arginase - BEC and arginasine, as well as darbepoetin demostrated that, with endotoxin-induced pathology, the highest probabilistic percentage of addiction was found in combination of rosuvastatin with arginasine (3 mg/kg) and darbepoetin (500 μg/kg), relatively, 31.9 ± 2.8 and 30.2 ± 2.9%. Discussion: The inhibitors of HMG-CoA reductase have demonstrated cardioprotective (decrease of adrenoreactivity and depletion of myocardial reserve, normalization of blood pressure) and endothelioprotective (amplification of eNOS expression, increase of NO) the attributes, which manifested itself as well as in monotherapy and in combination with some endothelioprotectors (L-arginine, arginasine, BEС, darbepoetin) in varying degrees.